2007
DOI: 10.1029/2006jd008265
|View full text |Cite
|
Sign up to set email alerts
|

Annual cycle of aerosol direct radiative effect over southeast Italy and sensitivity studies

Abstract: [1] Aerosol direct radiative effect (DRE) calculations are presented to illustrate the annual cycle of the aerosol impact on the radiative energy balance of the Earth-atmosphere system over southeast Italy. Meteorological parameters from radiosondes, aerosol vertical profiles by lidar, aerosol optical and microphysical properties by ground-based Sun/sky photometry and satellite (MODIS) derived data of solar surface albedo, all referring to the 2003-2004 years, constitute the necessary input to radiative transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 44 publications
5
23
0
Order By: Relevance
“…These SSA values are close to those observed in southern Spain (0.86-0.90) by Horvath et al (2002). Over southeastern Italy, Tafuro et al (2007) reported a value of 0.94 during summertime corresponding to anthropogenic particles. Finally, polluted particles transported over the Mediterranean basin also have relatively low values as reported by Markowicz et al (2002) over Crete (0.87) and by Di (0.79-0.83) over Lampedusa for two cases (25 and 27 May 1999) of "aged" anthropogenic aerosols originating from Europe.…”
Section: Mallet Et Al: Overview Of the Charmex/adrimed Summer 201supporting
confidence: 66%
See 1 more Smart Citation
“…These SSA values are close to those observed in southern Spain (0.86-0.90) by Horvath et al (2002). Over southeastern Italy, Tafuro et al (2007) reported a value of 0.94 during summertime corresponding to anthropogenic particles. Finally, polluted particles transported over the Mediterranean basin also have relatively low values as reported by Markowicz et al (2002) over Crete (0.87) and by Di (0.79-0.83) over Lampedusa for two cases (25 and 27 May 1999) of "aged" anthropogenic aerosols originating from Europe.…”
Section: Mallet Et Al: Overview Of the Charmex/adrimed Summer 201supporting
confidence: 66%
“…Numerous studies have documented the AOD for polluted anthropogenic Mediterranean aerosols at a local scale over southeastern France Roger et al, 2006), Spain Alados-Arboledas et al, 2003, the western Mediterranean (Lyamani et al, 2015), Greece (Chazette and Liousse, 2001;Gerasopoulos et al, 2003), the Greek island of Crete (Fotiadi et al, 2006), and Italy (Tafuro et al, 2007;Ciardini et al, 2012). Under polluted conditions, they report low to moderate AOD values ranging between 0.1 and 0.5 (at visible wavelengths).…”
Section: Mallet Et Al: Overview Of the Charmex/adrimed Summer 201mentioning
confidence: 99%
“…Although sensitivity studies demonstrated a relatively weak impact of the aerosol vertical distribution on radiative forcing at the surface or at clear-sky conditions (e.g. Tafuro et al, 2007), some impact can be expected under cloudy-skies for ToA DRE a , as (already slightly) absorbing aerosols (e.g. dust and pollution) above lower placed clouds (e.g.…”
Section: Aerosol Vertical Distributionmentioning
confidence: 99%
“…(Paltridge and Platt, 1976) are used. A discussion on the accuracy of individual AERONET retrievals is reported in Dubovik et al ( , 2002 and it is also recalled in Tafuro et al (2007). The number of measurements/month that have been properly weighted to retrieve monthly aerosol optical and microphysical properties at the selected AERONET sites, are given in Table 1.…”
Section: Surface Propertiesmentioning
confidence: 99%
See 1 more Smart Citation